173k views
2 votes
What is the process to solving -2(x-6)=-5(x+3)

User Hackoo
by
6.2k points

2 Answers

2 votes

-2(x-6)=-5(x+3)

Distributive property

-2x + 12 = -5x - 15

Addition property of equality (Add 5x to both sides)

3x + 12 = -15

Subtraction property of equality (Subtract 12 from both sides)

3x = -27

Division property of equality (Divide both sides by 3)

x = - 9

User Nodoid
by
5.5k points
3 votes

Step 1: Simplify both sides of the equation.

−2(x−6)=−5(x+3)

(−2)(x)+(−2)(−6)=(−5)(x)+(−5)(3)(Distribute)

−2x+12=−5x+−15

−2x+12=−5x−15

Step 2: Add 5x to both sides.

−2x+12+5x=−5x−15+5x

3x+12=−15

Step 3: Subtract 12 from both sides.

3x+12−12=−15−12

3x=−27

Step 4: Divide both sides by 3.

3x3=−273

x=−9

User Cavpollo
by
5.9k points